Don’t stop believing: the relative impact of internal alibi details on judgments of veracity - Keeping, Zak (Psychology, crime & law, 2017)
The relative impact of five alibi components on the assessment of alibi veracity was investigated using a policy-capturing methodology. Participants (N = 115) were instructed to assume the role of a homicide investigator and evaluate 32 alibis that varied on five dichotomous variables: Salaciousness; Legality; Change in Details; Superfluous Details; and Specific Details. Participants evaluated the believability of each alibi, and the likelihood of the alibi provider’s guilt. Results indicated that participants tended to disbelieve suspects when illegal or salacious behaviours were mentioned within the alibi. Few decision policies contained Change in Details, Superfluous Details, or Specific Details. The potential implications for alibi assessments during police investigations are discussed.